2017
DOI: 10.1063/1.4973475
|View full text |Cite
|
Sign up to set email alerts
|

Magneto-ionic effect in CoFeB thin films with in-plane and perpendicular-to-plane magnetic anisotropy

Abstract: The magneto-ionic effect is a promising method to control the magnetic properties electrically. Charged mobile oxygen ions can easily be driven by an electric field to modify the magnetic anisotropy of a ferromagnetic layer in contact with an ionic conductor in a solid-state device. In this paper, we report on the room temperature magneto-ionic modulation of the magnetic anisotropy of ultrathin CoFeB films in contact with a GdOx layer, as probed by polar micro-Magneto Optical Kerr Effect during the application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 27 publications
0
16
1
Order By: Relevance
“…Electric field-induced oxygen motion in magnetic materials (magneto-ionics) has recently revolutionized VCM since this mechanism may allow for a voltage-driven modulation of magnetic properties, such as coercivity, exchange bias field, or magnetic anisotropy, to a level never reached by any other magnetoelectric means (i.e., approaches i-iii) above). [6,[21][22][23][24][25][26][27][28][29][30][31][32][33][34] Magneto-ionics, with magnetoelectric coupling efficiencies of the order of 10 3 fJ/(V•m), might render energies per writing event as low as ≈10 −3 fJ = 1 aJ. [22,28] This represents energies two and five orders of magnitude lower than that required in complementary metal oxide semiconductor (CMOS) technology (≈10 −1 fJ per bit) and magnetic-based devices like magnetoresistive random access memories or hard disk drives (≈10 2 fJ per bit), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Electric field-induced oxygen motion in magnetic materials (magneto-ionics) has recently revolutionized VCM since this mechanism may allow for a voltage-driven modulation of magnetic properties, such as coercivity, exchange bias field, or magnetic anisotropy, to a level never reached by any other magnetoelectric means (i.e., approaches i-iii) above). [6,[21][22][23][24][25][26][27][28][29][30][31][32][33][34] Magneto-ionics, with magnetoelectric coupling efficiencies of the order of 10 3 fJ/(V•m), might render energies per writing event as low as ≈10 −3 fJ = 1 aJ. [22,28] This represents energies two and five orders of magnitude lower than that required in complementary metal oxide semiconductor (CMOS) technology (≈10 −1 fJ per bit) and magnetic-based devices like magnetoresistive random access memories or hard disk drives (≈10 2 fJ per bit), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…However, in ALD-grown high-κ layers such as STO, oxygen vacancies have been shown to impact the dielectric properties (such as permittivity) of the layer [31], and can contribute to the conductivity if they are mobile [32,33]. Large modulations of the magnetic anisotropy energy have been achieved using oxygen ion migration in high-κ GdO x , with a strength up to 11.6 pJ/Vm [34][35][36]. Even though the modulation coefficient on GdO x is particularly large, the ionic effect is slow and offers poor long term stability for memory applications.…”
Section: Introductionmentioning
confidence: 99%
“…Ion motion controlled by electric fields can exhibit large effects on the magnetic properties of materials, such as magnetic anisotropy [19], exchange bias [6], and remanent magnetization [7]. A recent study by Beach and coworkers showed that the diffusion of oxygen ions at the interface of GdO x and Co suppresses and regenerates the magnetic coercivity of this heterostructure [104].…”
Section: Control Of Optical and Magnetic Propertiesmentioning
confidence: 99%
“…Such conductivity modulation can also be achieved through changes in the bandwidth due to structural modifications [18]. In addition, the magnetic properties of materials can be altered through reversible ion doping mediated by electric fields [6,7,16,19]. In Figure 1(c), we present various emerging technologies utilizing ion doping-induced functionalities.…”
mentioning
confidence: 99%
See 1 more Smart Citation